Motor skills and parental support that affect physical education learning outcomes in elementary school students - Rizkal Rizkal; Ahmad Chaeroni; Wilda Welis; Zulbahri Zulbahri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to analyze the influence of motor ability and parental support on Physical Education learning outcomes, mediated by the adversity quotient of fifth and sixth-grade students at SDN 007 Sagulung, Batam. A quantitative approach with path analysis was employed. The sample consisted of 103 students selected through specific sampling techniques. Data collection instruments included a motor ability test (straight-line walking, shuttle run, sprinting, push-ups, and jumping), questionnaires for parental support and adversity quotient, and academic reports for learning outcomes. Data were processed using SPSS 26 through descriptive and inferential analysis. The results indicate that: (1) motor ability significantly affects learning outcomes (p<0.05); (2) parental support significantly affects learning outcomes (p<0.05); (3) adversity quotient significantly affects learning outcomes (p<0.05); (4) motor ability indirectly influences learning outcomes through adversity quotient by 12.85%; (5) parental support indirectly influences learning outcomes through adversity quotient by 9.59%; and (6) all variables simultaneously affect learning outcomes (Fcount 14.21>Ftable 3.14). In conclusion, adversity quotient serves as a crucial mediating variable that strengthens the impact of physical and environmental factors on students' academic achievement in.